DETERMINAÇÃO DAS FORMAS DO ARCO DENTÁRIO INFERIOR NA OCLUSÃO NORMAL NATURAL - Triviño, Tarcila (2005)
In order to determine the lower dental arch form of major incidence in the natural normal occlusion, a mathematic method associated with a polynomial function was applied on 63 study models of the lower arcade, which were selected among 6118 adolescents. All these patients were in permanent dentition, including second molars, with natural normal occlusion. A small pearl (bead) was glued to each dental element, which would simulate the orthodontic accessory and help to measure the distances between the center of the bead to axes x and y . The plaster models were, then, digitalized and the images were plotted on a computer program to obtain the polynomial function of sixth degree, as well as the graph of this function for the entire one hundred and twenty six curve segments, which were originated from the right and left sections of the images based on sixty three models. These segments were organized, according to the characteristics of the anterior curvature, in eight groups according with the eight different types of arch forms, which received the following denominations Form A, Form B, Form C, Form D, Form E, Form F, Form G, Form H. Each group was, then, divided into three sub-groups, which represented the sizes small, medium and large. The results indicated 23 most representative forms of the lower dental arch and a medium form for the natural normal occlusion.